2022
DOI: 10.3390/cancers14174139
|View full text |Cite
|
Sign up to set email alerts
|

Altered Adipokine Expression in Tumor Microenvironment Promotes Development of Triple Negative Breast Cancer

Abstract: Obesity is a remarkably important factor for breast carcinogenesis and aggressiveness. The implication of increased BMI in triple negative breast cancer (TNBC) development is also well established. A malignancy-promoting role of the adipose tissue has been supposed, where the adipocytes that constitute the majority of stromal cells release pro-inflammatory cytokines and growth factors. Alterations in adipokines and their receptors play significant roles in breast cancer initiation, progression, metastasis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…In studies related to GZMB, it was observed that in the PD-L1-positive group, Kaplan-Meier analysis revealed better recurrence-free survival (RFS) and OS in triple-negative breast cancer (TNBC) patients with high expression of GZMB (defined as ≥ 1% tumor-infiltrating lymphocytes (TILs) positive). Both RFS and OS were significantly prolonged in patients with high GZMB expression (RFS: P = 0.0220, OS: P = 0.0254) (Mizoguchi et al 2023). Multivariable Cox analysis also indicated better OS in patients with high expressions of PD-L1 and GZMB (hazard ratio: 0.25 (95% CI: 0.07-0.88), P = 0.03), suggesting that GZMB is a useful prognostic biomarker for PD-L1-positive TNBC patients (Mizoguchi et al 2023).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In studies related to GZMB, it was observed that in the PD-L1-positive group, Kaplan-Meier analysis revealed better recurrence-free survival (RFS) and OS in triple-negative breast cancer (TNBC) patients with high expression of GZMB (defined as ≥ 1% tumor-infiltrating lymphocytes (TILs) positive). Both RFS and OS were significantly prolonged in patients with high GZMB expression (RFS: P = 0.0220, OS: P = 0.0254) (Mizoguchi et al 2023). Multivariable Cox analysis also indicated better OS in patients with high expressions of PD-L1 and GZMB (hazard ratio: 0.25 (95% CI: 0.07-0.88), P = 0.03), suggesting that GZMB is a useful prognostic biomarker for PD-L1-positive TNBC patients (Mizoguchi et al 2023).…”
Section: Discussionmentioning
confidence: 96%
“…Both RFS and OS were significantly prolonged in patients with high GZMB expression (RFS: P = 0.0220, OS: P = 0.0254) (Mizoguchi et al 2023). Multivariable Cox analysis also indicated better OS in patients with high expressions of PD-L1 and GZMB (hazard ratio: 0.25 (95% CI: 0.07-0.88), P = 0.03), suggesting that GZMB is a useful prognostic biomarker for PD-L1-positive TNBC patients (Mizoguchi et al 2023). Additionally, a study found that high expression of GZMK in advanced melanoma significantly improved patients' PFS and OS (PFS: P = 0.04, OS: P = 0.01) (Wu et al 2021b).…”
Section: Discussionmentioning
confidence: 96%
“…These biochemical alterations have been linked to an increased risk of getting cancer, particularly TNBC. Furthermore, adipokines, which are signaling molecules generated by fat cells, may have a role in raising the risk of TNBC [ 34 ]. Hormonal treatment, which includes hormone replacement therapy and oral contraceptives, is another concern [ 7 , 35 ].…”
Section: Risk Factors For Triple Negative Breast Cancer (Tnbc)mentioning
confidence: 99%
“…Leptin and adiponectin interact with the tumor microenvironment (TME) [3,15]. Crosstalk between adipokines and TME components leads to the epithelial-mesenchymal transition (EMT) activation program, which is critical for tumor malignancy and metastasis [12].…”
Section: Introductionmentioning
confidence: 99%